Design And Implementation Of A Current Monitoring And Protection System Based On Pzem-004t For On-Grid Pv Systems - ilham, Enggie Faturrahman; Fadlilah, Umi (Universitas Muhammadiyah Surakarta, 2026)
The development of renewable energy systems, especially three-phase on-grid PLTS, requires accurate current monitoring and reliable protection. This study designs a monitoring and protection system using three PZEM-004T sensors to measure voltage, current, and power on each phase, with an ESP8266 as the central controller. A 100 WP solar panel supplies energy through a charge controller, battery, and three-phase inverter before being connected to the PLN grid. Experimental results show high measurement accuracy, with current errors of 0.00–0.13% and voltage errors of 0.07–0.15%. The system successfully detected load variations in the 7.10–8.30 A range and activated relay-based protection when overcurrent conditions occurred. Although testing reached only 8 A, the design supports currents up to 50 A. The integrated system provides effective real-time monitoring and automatic current cutoff, improving the safety and reliability of on-grid PLTS installations. Future work may include enhanced internet-based monitoring or long-range communication such as LoRa.